Cues and expressions - Thorbjörg Hróarsdóttir (Universitetet i Tromsø, 2004)
In special issue: Tromsø Working Papers in Language Acquisition A number of European languages have undergone a change from object-verb to verb-object order. We focus on the change in English and Icelandic, showing that while the structural change was the same, it took place at different times and different ways in the two languages, triggered by different E-language changes. As seen from the English viewpoint, low-level facts of inflection morphology may express the relevant cue for parameters, and so the loss of inflection may lead to a grammar change. This analysis does not carry over to Icelandic, as the loss of OV there took place despite rich case morphology. We aim to show how this can be explained within a cue-style approach, arguing for a universal set of cues. However, the relevant cue may be expressed differently among languages: While it may have been expressed through morphology in English, it as expressed through information structure in Icelandic. In both cases, external effects led to fewer expressions of the relevant (universal) cue and a grammar change took place.